PENGARUH PROMO DAN PELAYANAN TERHADAP KEPUASAN JAMAAH UMROH PADA PT. IRA WISATA TRAVEL HAJJ DAN UMRAH DI MEDAN - Hibahtullah, Mhd Habib; Firah, Al; Sahputra, Ngatno (Bisnis-Net, 2024)
This research aims to determine the effect of promotions and services on the satisfaction of Umrah pilgrims at PT. Ira Wisata Travel Hajj and Umrah in Medan. This research uses data analysis techniques in the form of quantitative analysis. The sample used in this research was 78 respondents. This research uses the variables Promotion, Service and Congregation Satisfaction. The results of the t test on the promo variable obtained tcount > ttable (2.961 > 1.991), so H0 was rejected and H1 was accepted, meaning that partially the promo variable had a positive and significant effect on congregation satisfaction at PT. Ira Wisata Travel Hajj & Umrah in Medan. The results of the t test on the variables obtained were tcount > ttable (2.004 > 1.991), so H0 was rejected and H2 was accepted, meaning that partially the service variable had a positive and significant effect on congregation satisfaction at PT. Ira Wisata Travel Hajj & Umrah in Medan. The results of the F test obtained Fcount > Ftable (19.145 > 3.119) meaning that simultaneously promos and services have a significant effect on congregation satisfaction at PT. Ira Wisata Travel Hajj & Umrah in Medan. The R test results show the Adjusted R Square value = 0.320 (32.0%) so that the promo and service variables can explain congregation satisfaction by 32.0% while the remaining 68.0% is influenced by other variables that are outside the model and cannot be detected in this research.